α-Copaene is an attractant, synergistic with quercivorol, for improved detection of Euwallacea nr. fornicatus (Coleoptera: Curculionidae: Scolytinae). - Paul E Kendra; David Owens; Wayne S Montgomery; Teresa I Narvaez; Gary R Bauchan; Elena Q Schnell; Nurhayat Tabanca; Daniel Carrillo (PLoS ONE)
The tea shot-hole borer, Euwallacea fornicatus Eichhoff, is an ambrosia beetle endemic to Asia and a pest of commercial tea, Camellia sinensis (L.) Kuntze. Recently, a complex of species morphologically similar to E. fornicatus has been recognized, which includes new pests established in Israel and the USA, both in California and Florida. Collectively termed E. nr. fornicatus, these cryptic species carry symbiotic Fusarium spp. fungi, some of which cause dieback disease in susceptible hosts, which include avocado, Persea americana Miller. Due to the threat to this economically important crop, research was initiated to evaluate efficacy of kairomone-based lures for detection of the beetle in Florida (termed the Florida tea shot hole borer, FL-TSHB). A series of field tests were conducted in 2016 in commercial avocado groves known to have FL-TSHB at various population levels. All tests evaluated lures containing quercivorol (p-menth-2-en-1-ol) and α-copaene, presented separately and in combination; and one test evaluated effect of trap type on beetle captures. In addition, electroantennography (EAG) was used to quantify female olfactory responses to lure emissions. This study identified (-)-α-copaene as a new attractant for FL-TSHB, equivalent in efficacy to quercivorol (the standard lure for Euwallacea detection in the USA); however, the combination of lures captured significantly more FL-TSHB than either lure alone. This combination resulted in synergistic attraction at two field sites and additive attraction at a third site. Sticky panel traps captured more FL-TSHB than comparably-baited Lindgren funnel traps. Females engaged in host-seeking flight from 11:00 to 16:00 hr (EST), with peak numbers observed between 12:00 and 13:00 hr. EAG analyses confirmed olfactory chemoreception of both kairomones, with a higher response elicited with the combination of volatiles. Results indicate that detection of pest E. nr. fornicatus in Florida can be improved by using a two-component lure consisting of p-menth-2-en-1-ol and (-)-α-copaene.